Reduced damage threshold for tungsten using combined steady state and transient sources - Morgan, T.W.; Zielinski, J.J.; Hensen, B.J.; Xu, H.Y.; Marot, L.; De Temmerman, G. (Journal of nuclear materials, 2013)
Divertor wall materials in future fusion devices will be subject to both high flux steady state plasma and transient ELM striking which could limit the lifetime of these plasma facing materials. A pulsed plasma source was therefore developed to reproduce these conditions. Laser irradiation of similar pulse length has been used to disambiguate between the effects of particle and heat loads compared with transient heating alone. A lowered threshold for damage of tungsten was observed in the case of simultaneous transient and steady state loads compared to transients alone, while surface damage was also enhanced with repeated laser irradiation following steady plasma exposure, compared to the two processes individually, indicating a synergistic enhancement of surface modification due to plasma exposure.